The C‐terminal extension of Mycobacterium tuberculosis Hsp16.3 regulates its oligomerization, subunit exchange dynamics and chaperone function. (12th January 2017) - Panda, Alok Kumar; Chakraborty, Ayon; Nandi, Sandip Kumar; Kaushik, Abhishek; Biswas, Ashis
Abstract : Mycobacterium tuberculosis is a human pathogen that secretes a major immunodominant antigen, namely Hsp16.3, throughout the course of infection. Hsp16.3 belongs to the small heat shock protein family and exhibits a molecular chaperone function that is important for the growth and survival of M. tuberculosis in host cell macrophages. The importance of the N‐terminal region for the structure and chaperone function of Hsp16.3 is well understood. However, the effect of the C‐terminal region on these properties is far from clear. Therefore, we cloned, over‐expressed and purified wild‐type and seven C‐terminal‐truncated mutant proteins of Hsp16.3. Mutants with deletions of one and two C‐terminal extension (CTE) residues had a structure and chaperone function similar to wild‐type protein. Intriguingly, deletion of three residues from the CTE triggered perturbation of the tertiary structure, dissociation of the oligomeric assembly (dodecamer to octamer and dimer), enhancement of subunit exchange dynamics and improvement in the chaperone function of Hsp16.3. Interestingly, these structural modulations (except oligomeric dissociation) as well as chaperoning strength reached their apex upon truncation of the entire CTE ( 1 41 RSTN 144 ). Further deletions from the C‐terminal region beyond the CTE increased only the degree of oligomeric dissociation, and the complete removal of this region made the protein into a dimer. Overall, our study suggests a 'new structural element' in the C‐terminal region, i.e. the C‐terminal extension, which plays an important role in the oligomerization, subunit exchange dynamics and chaperone function of Hsp16.3. Abstract : This study points out a structural element in the C‐terminal region of Hsp16.3, the C‐terminal extension, which plays an important role in its oligomerization, quaternary structure dynamics and chaperone function.